Emerging Roles of MHC Class I Region-Encoded E3 Ubiquitin Ligases in Innate Immunity - Jia, Xiuzhi; Zhao, Chunyuan; Zhao, Wei (Frontiers in Immunology, 2021)
The major histocompatibility complex (MHC) class I (MHC-I) region contains a multitude of genes relevant to immune response. Multiple E3 ubiquitin ligase genes, including tripartite motif 10 (TRIM10), TRIM15, TRIM26, TRIM27, TRIM31, TRIM38, TRIM39, TRIM40，and RING finger protein 39 (RNF39), are organized in a tight cluster，and an additional two TRIM genes (namely TRIM38 and TRIM27) telomeric of the cluster within the MHC-I region. The E3 ubiquitin ligases encoded by these genes possess important roles in controlling the intensity of innate immune responses. In this review, we discuss the E3 ubiquitin ligases encoded within the MHC-I region, highlight their regulatory roles in innate immunity, and outline their potential functions in infection and in inflammatory and autoimmune diseases.